Glucocorticoid mediated inhibition of LKB1 mutant non-small cell lung cancers - Huffman, Kenneth E.; Li, Long Shan; Carstens, Ryan; Park, Hyunsil; Girard, Luc; Avila, Kimberley; Wei, Shuguang; Kollipara, Rahul; Timmons, Brenda; Sudderth, Jessica; Bendris, Nawal; Kim, Jiyeon; et al. (Frontiers in Oncology, 2023)
The glucocorticoid receptor (GR) is an important anti-cancer target in lymphoid cancers but has been understudied in solid tumors like lung cancer, although glucocorticoids are often given with chemotherapy regimens to mitigate side effects. Here, we identify a GR mediated anti-cancer response in a subset of aggressive non-small cell lung cancers (NSCLCs) that harbor STK11/LKB1 mutations. Subcutaneous, orthotopic and metastatic NSCLC xenografts, biomarker-selected patient derived xenografts, and genetically engineered mouse models with KRAS/LKB1 mutant lung adenocarcinomas all showed marked anti-tumor responses with the glucocorticoid dexamethasone as a single agent or in combination with cisplatin. Mechanistically, GR activation triggers G1/S cell cycle arrest in LKB1 mutant NSCLCs by inducing the expression of the cyclin-dependent kinase inhibitor, p57(Kip2). GR mediated cell cycle arrest did not interfere with radiotherapy response in vitro or with platinum response in vivo and shows evidence of apoptotic activation in a NSCLC patient derived xenograft (PDX) STK11/LKB1 mutant model. These findings identify a previously unknown GR mediated therapeutic vulnerability in STK11/LKB1 mutant NSCLCs.